Harry Potter and the goblet of fire [video recording] - Rowling, J. K. (Burbank, CA : Warner Home Video, 2005)
Harry Potter is mysteriously entered into the Triwizard Tournament, a grueling contest among three wizarding schools in which he confronts a dragon, water demons and an enchanted maze only to find himself in Lord Voldemort's childhood forever and face challenges beyond their imagining.
Directed by Mike Newell ; Produced by David Heyman
Keywords: Potter, Harry (Fictitious character) -- Drama; Magical Adventure; Hogwarts School of Witchcraft and Wizardry (imaginary organization) -- Drama; Contests -- Drama